2007
DOI: 10.1002/app.25137
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of poly(3‐hydroxybutyrate) by exfoliated graphite nanoplatelets

Abstract: Poly(3-hydroxybutyrate) (PHB) has been shown to be efficiently nucleated by exfoliated graphite nanoplatelets (xGnP). The nucleating effect of xGnP was investigated using differential scanning calorimetry, optical microscopy and atomic force microscopy. Nonisothermal crystallization of PHB from the melt required lower activation energies for PHB containing 1 wt % and 3 wt % xGnP (À214 and À102 kJ/mol respectively) than for pure PHB (À60 kJ/mol). A kinetic study of the PHB/xGnP crystallization employing a modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…Exfoliated graphene nanoplatelets (xGnP), multiple graphene layers stacked to form platelets, were developed by a cost effective method as mentioned by Fukushima [7]. Researchers such as Kalaitzidou et al [8], Miloaga et al [9] and Pinto et al [10] have investigated the application of xGnP as a reinforcement filler with different polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Exfoliated graphene nanoplatelets (xGnP), multiple graphene layers stacked to form platelets, were developed by a cost effective method as mentioned by Fukushima [7]. Researchers such as Kalaitzidou et al [8], Miloaga et al [9] and Pinto et al [10] have investigated the application of xGnP as a reinforcement filler with different polymers.…”
Section: Introductionmentioning
confidence: 99%
“…This makes xGnP reinforced polymer nanocomposite manufacture products very feasible. xGnP has been incorporated into polymers such as epoxy, vinyl ester, polyamide, polypropylene, and polylactic acid for improving the mechanical and electrical properties [5][6][7][8]. It is found that xGnP not only improves the electrical conductivity of the host polymer, but also produces nucleation effects for thermoplastics.…”
Section: Introductionmentioning
confidence: 99%
“…Nano-expanded graphite has a nucleating effect on polyolefins (polyethylene (PE) [15], polypropylene (PP) [11,16]), biodegradable polyesters (poly(3-hydroxybutyrate) (PHB) [17] and polylactic acid (PLA) [18]). In the case of PP, it favors the crystalline β-phase which has improved mechanical properties compared to the crystalline α-phase.…”
Section: Conductive Fillermentioning
confidence: 99%